Contrasting mobility of arsenic and copper in a mining soil: A comparative column leaching and pot testing approach. (15th September 2022) - Cerqueira, Beatriz; Covelo, Emma F.; Rúa-Díaz, Sandra; Marcet, Purificación; Forján, Rubén; Gallego, José Luis R.; Trakal, Lukas; Beesley, Luke
Abstract: The remediation of legacy metal(loid) contaminated soils in-situ relies on the addition of [organic] amendments to reduce the mobility and bioavailability of metal(loid)s, improve soil geochemical parameters and restore vegetation growth. Two vermicomposts of food and animal manure waste origin (V1 and V2 ) were amended to an arsenic (As) and copper (Cu) contaminated mine soil (≤1500 mg kg −1 ). Leaching columns and pot experiments evaluated copper and arsenic in soil pore waters, as well as pH, dissolved organic carbon (DOC) and phosphate (PO4 3− ) concentrations. The uptake of As and Cu to ryegrass was also measured via the pot experiment, whilst recovered biochars from the column leaching test were measured for metal sorption at the termination of leaching. Vermicompost amendment to soil facilitated ryegrass growth which was entirely absent from the untreated soil in the pot test. All amendment combinations raised pore water pH by ∼4 units. Copper concentrations in pore waters from columns and pots showed steep reductions (∼1 mg L −1 ), as a result of V1 & V2 compared to untreated soil (∼500 mg L −1 ). Combined with an increase in DOC and PO4 3−, As was mobilised an order of magnitude by V1 . Biochar furthest reduced Cu in pore waters from the columns to <0.1 mg L −1, as a result of surface sorption. The results of this study indicate that biochar can restrict the mobility of Cu from a contaminated mine soil after other amendment interventions have been used to promote revegetation. However, the case of As, biochar cannot counter the profound impact of vermicompost on arsenic mobility. Highlights: Two vermicomposts and one biochar were amended to a metal(loid) rich mine soil. Vermicomposts promoted ryegrass growth, where biochar did not. Biochar was efficient for sorption of Cu from solution. No reductions in Cu uptake to ryegrass were achieved by the addition of biochar. High pH, Dissolved Organic Carbon and Phosphate generated by vermicompost mobilised As.